Derivation of four-point explicit block methods for direct solution of initial value problems of third order ordinary differential equations / Z. Omar, J.O. Kuboye and Y.A. Abdullah - Omar, Z.; Kuboye, J. O.; Abdullah, Y.A. (2015)
Two block methods for solving third order ordinary differential equations directly are presented. These methods are derived using two different approaches; direct integration and collocation. Both methods are capable of approximating the numerical solutions at four points simultaneously. The advantages and drawbacks of each method are also discussed.